Exergy analysis of turbulent flow for tubes of power plant feed water heaters and condensers. (23rd June 2009) - Ali, R.K.
The thermal performance of heat exchangers that are essential units in power plants can be substantially improved by a number of augmentation techniques. The entropy generation and exergy destruction rate due to the flow friction and heat transfer across temperature differences were proposed numerically to evaluate the benefits of utilisation of these techniques. Enhanced tubes with either dimples or spiral corrugations that are isothermally heated were investigated. The combination of spirally corrugated tubes with twisted tape inserts was also presented. In general, dimpled and spirally corrugated tubes and the combination of spirally corrugated tubes with a twisted tape substantially increase the percentage of temperature raise ratio and decrease the percentage of exergy destruction rate relative to smooth tubes. Increasing both the additional heat transfer area due to dimpling, and ridge height of corrugation increases the percentage of temperature raise ratio and decreases the exergy destruction rate. Also, the combination of corrugated tubes with twisted tapes is attractive as an augmentation technique based on exergy analysis, especially at low twisted tape length to inner tube diameter ratio, and high ridge height of corrugation for high Reynolds number.